1996
DOI: 10.1006/brln.1996.0018
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Illusions as Evidence for a Role of the Syllable in Adult Developmental Dyslexics

Abstract: This study investigated whether adult developmental dyslexics differ from normal controls in early stages of spoken language processing that in turn might be related to specific reading difficulties. Subjects were required to detect prespecified targets under dichotic presentation of auditory nonword pairs. The stimuli were made such that segment migrations were possible. The potential contribution of phonetic features, as well as that of phonemes and syllables, was investigated. The results showed that dyslex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Speech perception (SP) is the least explored aspect of phonological processing (de Gelder & Vroomen, 1996). However, several studies have shown that there are differences between children with RD and typical readers in auditory categorical perception tasks (e.g., Godfrey, Syrdal-Lasky, Millay, & Knox, 1981;Werker & Tees, 1987), in identifying monosyllabic words present in noise (Brady, Shankweiler, & Mann, 1983), and in discriminating between similar sounding word pairs (Reed, 1989).…”
mentioning
confidence: 99%
“…Speech perception (SP) is the least explored aspect of phonological processing (de Gelder & Vroomen, 1996). However, several studies have shown that there are differences between children with RD and typical readers in auditory categorical perception tasks (e.g., Godfrey, Syrdal-Lasky, Millay, & Knox, 1981;Werker & Tees, 1987), in identifying monosyllabic words present in noise (Brady, Shankweiler, & Mann, 1983), and in discriminating between similar sounding word pairs (Reed, 1989).…”
mentioning
confidence: 99%